2012
DOI: 10.2215/cjn.11171111
|View full text |Cite
|
Sign up to set email alerts
|

CKD and Coronary Collateral Supply in Individuals Undergoing Coronary Angiography after Myocardial Infarction

Abstract: SummaryBackground and objectives CKD patients have high mortality risk after myocardial infarction (MI). An adequate supply of coronary collaterals to the culprit vessel responsible for MI is associated with reduced risks of death and complications. Whether a diminished supply of collaterals contributes to the high risk in CKD patients is uncertain.Design, setting, participants, & measurements Quantitative coronary angiography was performed in a consecutive series of individuals with (n=58) and without (n=165)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
1
3
0
1
Order By: Relevance
“…10 On the other hand, Charytan et al, who compared 58 patients with impaired renal function with 165 patients with preserved renal function, found that there was no association between renal impairment and coronary CC. 36 Our study not only demonstrated a significant difference in CCs among patients with graded impairment in renal function but also showed that this impairment was significant below a specific eGFR. Our findings showed that patients with eGFR <60 mL/min/1.73 m 2 were less likely to have CCs than patients with eGFR >60 mL/min/1.73 m 2 .…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…10 On the other hand, Charytan et al, who compared 58 patients with impaired renal function with 165 patients with preserved renal function, found that there was no association between renal impairment and coronary CC. 36 Our study not only demonstrated a significant difference in CCs among patients with graded impairment in renal function but also showed that this impairment was significant below a specific eGFR. Our findings showed that patients with eGFR <60 mL/min/1.73 m 2 were less likely to have CCs than patients with eGFR >60 mL/min/1.73 m 2 .…”
Section: Discussionsupporting
confidence: 55%
“…Although renal impairment has long been associated with higher risk of cardiovascular events such as MI or post-MI complications, 32 it is not well known whether this stems from its effect on the CC circulation. Animal models have shown that uremia is associated with impaired ischemia-induced angiogenesis and reduced myocardial capillary density.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Charytan et al hypothesized that CKD patients might have less collateral blood supply to ischemic area of the myocardium and this hypothesis might partially explain why CKD patients have much worse CV outcomes and death. However, this study failed to prove this hypothesis because both CKD patients and subjects without CKD had similar culprit artery collateral supply (25% versus 27.2%, resp., P = 0.76) [ 25 ].…”
Section: Pathophysiology Of Cad In Ckdmentioning
confidence: 99%
“…При хронической болезни почек (ХБП) нередко определяется микроваскулярная дисфункция, приводящая к ишемии миокарда [5,6]. У пациентов со сниженной почечной функцией, атеросклеротическая бляшка более насыщена липидами и менее насыщена соединительной тканью, что значимо увеличивает ее ранимость [7]. В связи с этим ХБП сопровождается более тяжелым коронарным атеросклерозом [8,9].…”
Section: Introductionunclassified